Extracellular signal-regulated kinase activation during cardiac hypertrophy reduces sarcoplasmic/endoplasmic reticulum calcium ATPase 2 (SERCA2) transcription - Huang, Haiyan (2014)
Pathologic cardiac hypertrophy can lead to heart failure, but the mechanisms involved are poorly understood. SERCA2 is critical for normal cardiac calcium handling and function and SERCA2 mRNA and protein levels are reduced by cardiac hypertrophy. We hypothesized that Extracellular Signal-regulated Kinase (ERK) 1/2 activation during hypertrophy reduced SERCA2 transcription. Using a neonatal rat ventricular myocyte model of hypertrophy, we found that pharmacologic inhibitors of ERK activation preserve SERCA2 mRNA levels during hypertrophy. ERK activation is sufficient to reduce SERCA2 mRNA. We determined that ERK represses SERCA2 transcription via nuclear factor-kappaB (NFkB), and activation of NFkB is sufficient to reduce SERCA2 mRNA in cardiomyocytes. This work establishes novel connections between ERK, NFkB, and SERCA2 repression during cardiac hypertrophy. This mechanism may have implications for the progression of hypertrophy to heart failure.